2020
DOI: 10.1111/1462-2920.15180
|View full text |Cite
|
Sign up to set email alerts
|

Major changes in grapevine wood microbiota are associated with the onset of esca, a devastating trunk disease

Abstract: Esca, a major grapevine trunk disease in old grapevines, is associated with the colonization of woody tissues by a broad range of plant pathogenic fungi. To identify which fungal and bacterial species are involved in the onset of this disease, we analysed the microbiota from woody tissues of young (10-yearold) grapevines at an early stage of esca. Using meta-barcoding, 515 fungal and 403 bacterial operational taxonomic units (OTUs) were identified in woody tissues. In situ hybridization showed that these fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
65
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 41 publications
15
65
2
Order By: Relevance
“…in the non-necrotic tissue of esca-diseased grapevines. This was based on our results and those from Bruez et al on Cabernet-Sauvignon cultivar in a Bordeaux vineyard, we hypothesized that the taxonomic composition of bacterial communities from grapevine woody tissues strongly differs according to cultivar or region in France [11,28]. Further samplings are needed to confirm if differences in bacterial taxa composition of trunk woody tissues occur according to the vineyard in different European regions.…”
Section: Bacterial Microbiota Colonizing Woody Tissues From Esca-diseased Grapevinessupporting
confidence: 61%
See 1 more Smart Citation
“…in the non-necrotic tissue of esca-diseased grapevines. This was based on our results and those from Bruez et al on Cabernet-Sauvignon cultivar in a Bordeaux vineyard, we hypothesized that the taxonomic composition of bacterial communities from grapevine woody tissues strongly differs according to cultivar or region in France [11,28]. Further samplings are needed to confirm if differences in bacterial taxa composition of trunk woody tissues occur according to the vineyard in different European regions.…”
Section: Bacterial Microbiota Colonizing Woody Tissues From Esca-diseased Grapevinessupporting
confidence: 61%
“…The DNA extraction protocol used here was similar to that of Bruez et al [ 11 , 28 ]. SSCP analysis was performed on samples collected both in September 2014 and September 2015.…”
Section: Methodsmentioning
confidence: 99%
“…(S19) is an excellent biocontrol candidate against P. chlamydospora (Haidar et al, 2016b). In terms of whole bacterial communities, Bruez et al, 2015 andBruez et al, 2020 were the first to show that specific complexes of bacteria colonise the different tissues (necrotic and non-necrotic) of grapevine expressing, or not, Esca-foliar symptoms. If we put together our findings on P. agglomerans and Paenibacillus sp., and the bacteria communities colonising the grapevine wood, it can be suggested that grapevine tissues comprise a reservoir of beneficial bacteria with potential biocontrol properties against GTD pathogens; this is supportedby recent reports of bacteria which had been isolated from a vineyard having biocontrol activity, such as Bacillus sp., Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of antagonistic microorganisms against GTD fungi is of prime importance. Recent studies have revealed high fungal and bacterial diversity in different types of wood tissue -necrotic or not -of both asymptomatic and esca-diseased grapevine (Bruez et al, 2015;Zarraonaindia et al, 2015;Berlanas et al, 2019;Kraus et al, 2019). The interactions of microbial communities could be beneficial for their host plant by, for example, increasing its resilience against certain pathogens (Compant et al, 2013;Pacifico et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant findings have been obtained on grapevine leaf stripe disease, a widely spread wood disease of Esca complex, regarding phytotoxic metabolites, symptom expression and their management [8,9]. However, the relationship of GTDs with biotic and abiotic stresses [10][11][12][13], the expression of symptoms and their effective management requires further investigation [6,14,15]. The main GTDs that threaten vineyards worldwide are Eutypa dieback (ED), Esca complex diseases, and Botryosphaeria dieback (BD), all of them caused by pathogenic fungi belonging to different families.…”
Section: Introductionmentioning
confidence: 99%